Highly oriented quasi-2D layered tin halide perovskites with 2-thiopheneethylammonium iodide for efficient and stable tin perovskite solar cells. (12th January 2022) - Xu, Yanting; Jiang, Ke-Jian; Wang, Pengcheng; Gu, Wei-Min; Yu, Guang-Hui; Zhou, Xueqin; Song, Yanlin
Abstract : The addition of TEAI can induce oriented growth of perovskite films and enhance the efficiency with high stability. Abstract : 3D tin-based halide perovskites are promising light absorbers for perovskite solar cells (PSCs) due to their non-toxicity, suitable optical band gaps, and excellent optoelectronic properties. However, the inherent rapid crystallization and easy oxidation of Sn 2+ to Sn 4+ in 3D perovskites result in a low power conversion efficiency (PCE) and poor stability of tin perovskite solar cells compared with the lead counterparts. In this report, quasi-2D hybrid tin-based perovskite films are fabricated by using 2-thiopheneethylammonium (TEA + ) as the spacer cation in MASnI3 (MA: CH3 NH3 + ), leading to the formation of quasi-2D perovskite films with high orientation and a low content of Sn 4+ . As a result, the perovskite solar cells show a considerable power-conversion efficiency of 6.8%, which is among the highest values reported for MASnI3 -based solar cells. Moreover, the devices exhibited excellent stability compared with the device without TEAI.